A apropriação da Região Leste de Goiânia pelo capital - Mendes, Julianna Fernandes (2023)
This doctoral dissertation is part of the Line of Research: Power, Sertão and Identities of the Graduate Program in History of the Federal University of Goiás, proposing to investigate The appropriation of the eastern region of Goiânia by the capital. The first chapter seeks to understand the control of urban space, with the subsequent release of allotments, as well as the division of social classes in the urban of Goiânia. In addition, it sought to analyze this premise based on data from the SFH, BNH and COHAB, verifying that the housing policies promoted during the military dictatorship period reinforced the segregation of urban space and legal insecurity of tenure. Then, in the second chapter, we try to analyze Real Estate Capital and the expansionist reform towards the east region, reinforcing how the public power together with the private initiative designed and implemented public policies for the urban expansion area of Goiânia. Thus, delimiting the eastern region by demonstrating its specificities was important to analyze the reason for urban expansion to move towards the eastern region in the early 1970s. The study of critical geography and urban history allowed for a discussion between Santos, Moyses, Harvey, Lefebvre, Haesbaert and Raffestin on the transformation of Goiânia from space to territory as power. In the same sense, we demonstrate through legislation how the expansionist compass was projected towards the eastern region. The third chapter called the appropriation of the eastern region of Goiânia by the capital, we seek to understand, not only the territorial appropriation, but also the appropriation of other essential assets for urban and community development. It was up to us to verify who the owners of the eastern region were, we arrived at the Louza family as owners of most of the Gameleira Farm which was acquired in July 1943 and, later, from 1950 onwards, they carried out the subdivision of land for the construction of the Jardim Goiás neighborhood. The discussion was still permeated about the urban voids and the appropriation by financialized capital that evidenced the modus operandi of real estate speculation.